PHARMACOGNOSTIC, PHYSICO-CHEMICAL AND PHYTOCHEMICAL EVALUATION OF PACHYGONE OVATA (POIR.) MIERS EX HOOK. F. ET THOMS LEAF - SHIRIN MARAHEL,; BEHROUZ JALALI GHASSAM,; UMESHA S, (International Journal of Pharma and Bio Sciences, 2014)
Pachygone ovata being one of the unexplored species of the menispermaceae family has gained our attention to this study. Macroscopic features highlighted ovatelanceolate leaves with an entire margin showing reticulate veination, microscopic analyses indicated anomocytic type of stomata on the abaxial surface, presence of starch grains in the parenchyma layer and unicellular and multicellular trichomes on the midrib. Physico-chemical parameters were analyzed for further standardization, which indicated low amounts of moisture (3.45) and low amounts of acid insoluble ash (2.01). Fluorescence and phytochemical studies helped in concluding the nature of the compounds and secondary metabolites present in the plant material, confirming the presence of flavonoids, triterpenoids, glycosides and alkaloids. Lowest phenolic content was recorded in the hexane extract (85 ± 4 μg GAE/mg dw) while the highest was found to be in the methanol extract of P.ovata (389 ± 4 μg GAE/mg dw). Only ethnopharmalogical evidences in this age cannot suffice for the usage of plants, it is now a prerequisite to authenticate the plants for safer health care, therefore the details included in this paper will help in authentication of this plant in terms of identification and quality assurance.